Micropower front-end interface for differential-capacitive sensor systems - Constandinou,TG; Georgiou,J; Toumazou,C (Electronics Letters, 2008)
A front-end circuit for interfacing to differential capacitive sensors, including certain microelectromechanical systems, is presented. The system combines a self-resetting, biphasic integrator with a difference timer, producing a word parallel output representing the differential capacitance. The measurable capacitance range is tunable by means of an input current bias and system clock frequency. For an input bias of 10 nA and system clock of 128 KHz, the measurable capacitance range is +/-5pF (to 8 bit resolution) consuming below 26 µW total system power.